Aqueous electrolyte-gated solution-processed metal oxide transistors for direct cellular interfaces - Kang, Dong Hee; Choi, Jun Gyu; Lee, Won June; Heo, Dongmi; Wang, Sungrok; Park, Sungjun; Yoon, Myung Han (APL Bioengineering, 2023)
Biocompatible field-effect-transistor-based biosensors have drawn attention for the development of next-generation human-friendly electronics. High-performance electronic devices must achieve low-voltage operation, long-term operational stability, and biocompatibility. Herein, we propose an electrolyte-gated thin-film transistor made of large-area solution-processed indium-gallium-zinc oxide (IGZO) semiconductors capable of directly interacting with live cells at physiological conditions. The fabricated transistors exhibit good electrical performance operating under sub-0.5 V conditions with high on-/off-current ratios (>107) and transconductance (>1.0 mS) over an extended operational lifetime. Furthermore, we verified the biocompatibility of the IGZO surface to various types of mammalian cells in terms of cell viability, proliferation, morphology, and drug responsiveness. Finally, the prolonged stable operation of electrolyte-gated transistor devices directly integrated with live cells provides the proof-of-concept for solution-processed metal oxide material-based direct cellular interfaces.
Keywords: Aqueous electrolyte; Cellular interfaces; Field-effect transistor; Gallium zinc oxides; Human-friendly; Live cell; Metal-oxide; Oxide transistors; Performance; Solution-processed